2011
DOI: 10.1139/f10-139
|View full text |Cite
|
Sign up to set email alerts
|

Historic divergence with contemporary connectivity in a catadromous fish, the estuary perch (Macquaria colonorum)

Abstract: The estuary perch ( Macquaria colonorum ) represents an important model for assessing how historical changes in coastal geomorphology and current oceanographic and estuarine conditions may have impacted connectivity in a catadromous fish. A fragment of the mitochondrial control region and six microsatellite DNA markers were used to clarify connectivity in 17 populations (n = 354) of estuary perch from the southeast and southern coasts of Australia. The mtDNA data showed a latitudinal disjunction in haplotype f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 81 publications
6
11
0
Order By: Relevance
“…382 Similar IBD relationships have been reported for other coastline restricted species (Keenan, 383 1994; Jerry & Baverstock, 1998;Shaddick et al, 2011;Schmidt et al, 2014). Lack of IBD for 384 the CEQ group may be attributed to insufficient number of population samples available for (Table 4).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…382 Similar IBD relationships have been reported for other coastline restricted species (Keenan, 383 1994; Jerry & Baverstock, 1998;Shaddick et al, 2011;Schmidt et al, 2014). Lack of IBD for 384 the CEQ group may be attributed to insufficient number of population samples available for (Table 4).…”
supporting
confidence: 60%
“…In this study, a strong IBD relationship 380 was identified among the SEQ populations, but not among CEQ populations. This suggests that 381 for SEQ populations, dispersal, when it occurs, is more likely between nearby catchments.382 Similar IBD relationships have been reported for other coastline restricted species (Keenan, 383 1994; Jerry & Baverstock, 1998;Shaddick et al, 2011;Schmidt et al, 2014). Lack of IBD for 384 the CEQ group may be attributed to insufficient number of population samples available for (Table 4).…”
mentioning
confidence: 53%
“…; Shaddick et al. ) and can mask some of the historical influences on, or complicate inferences regarding, divergence and population structure (Turgeon and Bernatchez ; Adams et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, within NSW, the two species are thought to live in spatial and temporal isolation, thus inhibiting prolific hybridization in the rivers where they coexist. Both M. novemaculeata and M. colonorum, however, are capable of migrating considerable distances through coastal marine waters (Chenoweth & Hughes, 1997; Jerry & Baverstock, 1998; Jerry et al , 1999; Shaddick et al , 2011) facilitating the movement of hybrid individuals along the coastline. This may explain the presence of three putative hybrids outside the range of M. novemaculeata in the Tarwin, Glenelg and Barham Rivers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved using oligonucleotide primers A and E (Lee et al , 1995) and PCR conditions and protocols outlined in Beheregaray & Sunnucks (2001). Mitochondrial DNA control region sequences were aligned by eye with existing M. novemaculeata and M. colonorum mtDNA control‐region data sets (Jerry & Baverstock, 1998; Shaddick et al , 2011).…”
Section: Methodsmentioning
confidence: 99%